TOURISM VILLAGE DEVELOPMENT THROUGH SUSTAINABLE AGRO-TOURISM: VILLAGE PLACEMAKING (CASE STUDY SIBETAN VILLAGE, BEBANDEM DISTRICTS, KARANGASEM REGENCY â BALI) - Made Diah Ayu Kendran, Ni
The topographical diversity in Kab. Karangasem makes this area has attractive tourism potential. One of them comes from the agriculture sector, especially salak agriculture product. Salak agriculture in Kab. Karangasem was famous sector because of its thick flesh and uniqueness taste. In the terms of its history, the existence of the Balinese salak plant was estimated come from Sibetan Village, Bebandem District, originally cultivated by the founder of the village named Jero Dukuh Sakti. The main reason for the development of salak in this village was up to 85% of the total area village, because the salak was one of the complementary fruits in the traditional ceremonies by local community. This situation makes Sibetan Village be the largest area in Bali that producing salak, whose varieties have been designated as national superior products. The great potential of varieties salak in Sibetan Village, in the fact didn’t able to be developed optimally. This situation can be seen from the disadvantage experienced by the farmers even when in the harvest season. If this condition left away, the existence of salak plantations in Sibetan Village will be decrease until finally disappear. Therefore, the situation needed a solution to improve the standard living of farmers as well as a conservation way to existence the Balinese salak plant, that was by developing a sustainable tourism village. The tourism development and design scheme that applied in this case study was the development of a tourism village with a placemaking design approach and sustainable tourism, through the design components had been formulated. The design components were implemented in the form of design criteria based on the results of the analysis of preferences, motivations, activities, and the desire of tourists to visit agro-tourism areas. The final result of the design was that the character of a sustainable tourism village can be implemented using village placemaking for sustainable agro-tourism component. The natural attraction factor was the dominant factor that can attract tourists to visit again in the agro-tourism area. It has side implications for the design that must maintain aspects of natural sustainability in physical form of environment and cultural environment where the humans live in. This thesis aimsto being a design solution in the development of tourism village in Sibetan with its potential and character, especially in the agricultural sector. This character will be makes identity of the village that distinguishes it from others village in Bali.